2014
DOI: 10.14391/ajhs.7.60
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Special Needs Education Assessment Tool (SNEAT) to Evaluate the Educational Outcome of Special Needs Education

Abstract: It is currently difficult to find the tools to assess educational outcome in the field of special needs education. Therefore, this study aimed to develop the tool to evaluate the educational outcome of special needs education, called as the Special Needs Education Assessment Tool(hereafter, the SNEAT), that will enable teachers to evaluate their classes according to the changes of children with disabilities; for the development of the SNEAT, its content validity was verified with the draft of the SNEAT. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…They aim to help children with disabilities live an independent life by enabling them to acquire the knowledge, skills, attitudes, and habits required to overcome difficulties in learning and living, and have played an important role in A. Kohara et al 242 the education of children with disabilities (Ministry of Education, Culture, Sports, Science and Technology 2009). Kohara et al (2014a) first verified the content validity of SNEAT by conducting an expert survey among researchers on special needs education and QOL and in-service teachers. The follow-up survey that they conducted on the content validity of SNEAT among 89 in-service teachers in Okinawa Prefecture in Japan also showed that over 90% of the respondent teachers agreed that the contents of SNEAT are valid.…”
mentioning
confidence: 99%
“…They aim to help children with disabilities live an independent life by enabling them to acquire the knowledge, skills, attitudes, and habits required to overcome difficulties in learning and living, and have played an important role in A. Kohara et al 242 the education of children with disabilities (Ministry of Education, Culture, Sports, Science and Technology 2009). Kohara et al (2014a) first verified the content validity of SNEAT by conducting an expert survey among researchers on special needs education and QOL and in-service teachers. The follow-up survey that they conducted on the content validity of SNEAT among 89 in-service teachers in Okinawa Prefecture in Japan also showed that over 90% of the respondent teachers agreed that the contents of SNEAT are valid.…”
mentioning
confidence: 99%